Rhoicosphenia johannessoniae (Bacillariophyceae), a new diatom from the Swedish coast of the Baltic Sea - AL-HANDAL, ADIL Y.; LEVKOV, ZLATKO; WULFF, ANGELA (Magnolia Press, 2023)
Rhoicosphenia is a relatively small diatom genus regarding the number of species and the genus is characterized by its wedge-shaped frustule and heterovalvar structure. It is one of the few genera that is distributed in both marine and freshwater habitats. Few species of Rhoicosphenia are known along the stretched Baltic Sea coast of Sweden. The present study describes a new epiphytic species of Rhoicosphenia from the brackish water of Grisslehamn in the northern part of the Baltic Sea. Rhoicosphenia johannessoniae sp. nov. appears closely related to R. baltica, but differs in having more elongated and protracted base pole, densely packed areolae and a central area located below the central part of the valve. Detailed descriptions of the species based on light and electron microscopy, as well as a comparison with related taxa, are provided. The present work is part of a larger project aiming to study the littoral diatoms of Sweden. The finding of this species, together with other species previously described within the project, will add to our knowledge of the diatom assemblages of the Baltic Sea which seems to have a richer flora than earlier anticipated.